Measurement of vapor pressure of palm oil constituents under vacuum - Morad, Noor Azian; Idrees, Mohammad; Abu Hassan, Adilah (Jawatankuasa Penyelidikan & Perundingan, Fakulti Kej. Kimia & Kej. Sumber Asli, UTM, 1994)

(untitled)
Vapor pressure is one of the most important properties in chemical process design for unit operations like distillation, extraction an absorption processes. Even though, vapor pressure data for most of the commonly used chemical compounds are available in the literature and the data bank is continuously being updated, reliable vapor pressure data for vegetable oils are scarce. Vapor pressure of vegetable oils are not easily determined due to its complex nature (chemical composition) and temperature sensitivity. The vapor pressure measurements of all phlegmatic liquids including oils and its main constituent triglycerides, require a method which impose a minimum of thermal hazard to the substance under examination. It is also suggested that the vapor pressure of vegetable oils may be determined from the data on its constituent triglycerides by suitable interpolation/extrapolation. This paper discusses methods of determining vapor pressure of some of the major components found in palm oil. Some intricate problems related to the temperature measurement and instrumentation under very low pressures are also indicated. Preliminary results of this investigation on the vapor pressure of the triglycerides are presented.